Effects of copper on CHO cells: Insights from gene expression analyses. (21st January 2014) - Yuk, Inn H.; Zhang, Jitao David; Ebeling, Martin; Berrera, Marco; Gomez, Natalia; Werz, Silke; Meiringer, Christoph; Shao, Zhixin; Swanberg, Jeffrey C.; Lee, Kelvin H.; Luo, Jun; Szperalski, Berthold
<x xml:space="preserve">Abstract</x> Copper concentration can impact lactate metabolism in Chinese Hamster ovary (CHO) cells. In our previous study, a 20‐fold increase in initial copper concentration enabled CHO cultures to shift from net lactate production to net lactate consumption, and achieve higher cell growth and productivity. In this follow‐up study, we used transcriptomics to investigate the mechanism of action (MOA) of copper that mediates this beneficial metabolism shift. From microarray profiling (days 0–7), the number of differentially expressed genes increased considerably after the lactate shift (>day 3). To uncouple the effects of copper at early time points (days 0–3) from that of lactate per se (>day 3), and to validate microarray hits, we analyzed samples before the lactate shift by RNA‐Seq. Out of 6, 398 overlapping genes analyzed by both transcriptomic methods, only the early growth response 1 gene—coding for a transcription factor that activates signaling pathways in response to environmental stimuli—satisfied the differential expression criteria (fold change ≥1.5; P < 0.05). Gene expression correlation and biological pathway analyses further confirmed that copper differences exerted minimal transcriptional impact on the CHO cultures before the lactate shift. By contrast, genes associated with hypoxia network and oxidative stress response were upregulated after the lactate shift. These upregulations should boost cell proliferation and survival, but do not account for the preceding shift in lactate metabolism. The findings here indicate that the primary MOA of copper that enabled the shift in lactate metabolism is not at the transcriptional level. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:429–442, 2014